An epidemiological study on the prevalence of hallucinations in a general-population sample: Effects of age and sensory modality. (February 2019) - Larøi, Frank; Bless, Josef J.; Laloyaux, Julien; Kråkvik, Bodil; Vedul-Kjelsås, Einar; Kalhovde, Anne Martha; Hirnstein, Marco; Hugdahl, Kenneth
Highlights: Epidemiological studies have repeatedly shown that a significant minority of the general population have experienced hallucinations. However, no previous research has examined whether there is an effect of age on this prevalence. Based on a large, randomly selected and representative sample of the general population, a significant main-effect of age was observed (decreased with age). Anxiety and depression levels partially mediated the effect of age on hallucinations. Abstract: Epidemiological studies have repeatedly shown that a significant minority of the general population have experienced hallucinations, however, a potential effect of age on the prevalence of hallucinations in the general population has never been previously examined in a specific study. The aim of the present study was thus to examine the effects of age and sensory modality on hallucination prevalence in a general population sample. A large, randomly selected and representative sample of the Norwegian population completed measures assessing different hallucination modalities (auditory, visual, olfactory, and tactile) and types (sensed presence and hypnagogic/hypnopompic hallucinations). Three age groups were identified and compared: young (19–30 years), middle (31–60) and old (61–96). There was a significant main-effect of age for all hallucination modalities and types, whereby hallucination prevalence significantly decreased with age. We also found that anxiety partially mediated the effect of age on hallucinations whilst depression was a partial suppressor. Concerning the co-occurrence of hallucination modalities, there was very little co-occurrence of auditory and visual hallucinations in all three age groups. In summary, a main-effect of age for hallucination prevalence was observed. Furthermore, individuals reported a more diverse variety of hallucination modalities compared to what is commonly reported in clinical populations.